(untitled) (Novateur Publications, 2024)
This monograph describes the scientific research carried out in the direction of evaluating the early rehabilitation measures, their procedure and effectiveness during the acute period of ischemic stroke on the background of diabetes. The information presented in the monograph meets the standards of treatment and rehabilitation, in which the methods of assessing the condition of stroke patients and performing the verticalization procedure are described in fluent language and many problems are emphasized. The manual can be used in practice as an important guide for medical institutions, clinical residents, masters, neurologists, rehabilitologists and neuroreanimatologists.